2001
DOI: 10.4141/a00-071
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses to climatic demands of dairy heifers housed outdoors

Abstract: Redbo, I., Ehrlemark, A. and Redbo-Torstensson, P. 2001. Behavioural responses to climatic demands of dairy heifers housed outdoors. Can. J. Anim. Sci. 81: 9-15. The aim of the present study was to investigate the behavioural responses to different climatic demands of growing dairy heifers, during winter at a latitude of 60°N. Two groups (n = 11, 12) of yearling dairy heifers were housed in two similar 3-ha enclosures, characterised by deciduous forest, ley and pasture. Each enclosure also contained a lying ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…Dairy heifers adapt well to cold outdoor conditions if provided with shelter and a dry lying (Redbo et al, 2001), and out-wintering mature cattle on forage crops can achieve similar levels of animal performance to housing (Keogh et al, 2009). Out-wintering systems in Great Britain are farmer-led innovations (Barnes et al, 2013), therefore a survey of these farmers was conducted to assess current practice with a view to informing dairy farmers who are considering employing this system of heifer rearing.…”
Section: Resultsmentioning
confidence: 99%
“…Dairy heifers adapt well to cold outdoor conditions if provided with shelter and a dry lying (Redbo et al, 2001), and out-wintering mature cattle on forage crops can achieve similar levels of animal performance to housing (Keogh et al, 2009). Out-wintering systems in Great Britain are farmer-led innovations (Barnes et al, 2013), therefore a survey of these farmers was conducted to assess current practice with a view to informing dairy farmers who are considering employing this system of heifer rearing.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, cold conditions or absence of shelters have affected animal performance negatively (e.g. Birkelo et al, 1991;Delfino and Mathison, 1991;Kubisch et al, 1991) or have changed animal behaviour (Redbo et al, 2001). On the contrary, McCarrick and Drennan (1972a,b) and Redbo et al (1996) reported no negative effects on animal health and live weight gain.…”
Section: Introductionmentioning
confidence: 96%
“…Exposure to adverse environmental conditions induces a variety of behavioural and physiological responses associated with impaired performance, and thus animal housing aims to eliminate or moderate negative effects of the environment (National Research Council (NRC), 1981). Cows exposed to harsh weather spend less time feeding (Redbo et al, 2001;Tucker et al, 2007 ) and more time standing (Kiernan, 2004;Tucker et al, 2007) compared with sheltered cows. Cold conditions and excessive standing causes an increase in the secretion of cortisol, particularly in thin cows (Fisher et al, 2002;Tucker et al, 2007), which is in turn associated with reduced growth (Purchas et al, 1980).…”
Section: Introductionmentioning
confidence: 99%